PENGUATAN PERAN UNIT KESEHATAN SEKOLAH DALAM MENINGKATKAN PERILAKU HIDUP BERSIH DAN SEHAT DI SDN 17 GURUN LAWEH KECAMATAN NANGGALO - Syafrawati syafrawati; Mery Ramadani (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
It is important that School Health Unit (UKS) activities are carried out in schools in accordance with existing regulations. Problems that often arise in the implementation of UKS include that schools already have a special room for UKS activities, but its utilization is not optimal and cadres of students have not been formed on an ongoing basis to become UKS administrators. The implementation of the UKS at SDN 17 Gurun Laweh has not run optimally because the UKS cadres have not been active and the infrastructure is lacking. Therefore it is necessary to carry out counseling and practical implementation of UKS as training material for UKS cadres at SDN 17 Gurun Laweh. The activities carried out were in the form of health counseling using the lecture method (delivering prepared material) using PowerPoint on balanced nutrition, undernutrition, excess nutrition (obesity), and First Aid in Accidents (P3K), as well as practice when delivering first aid material. To evaluate the activities, a pre-test and post-test were carried out before and after the delivery of the material. After counseling, there was a significant increase in student's knowledge of the material presented from an average score of 75.3 to 90. It was found that knowledge that experienced the most significant increase was about the 4 pillars of balanced nutrition and about first aid kits. With the results of this activity, it is hoped that the prospective UKS cadres will be able to return to activity and that the UKS can run according to its functions. It is suggested that there is a need for continuing training for UKS cadres in collaboration with the local public health center for training activities.